Teknik Pengendalian Mutu Dengan Menggunakan Metode Diagram Pareto Dalam mencapai Customer Satisfaction - Rachmasari Pramita Wardhani; Lukman; Selvia Sarungu; Siti Norhidayah (JURNAL TEKNOSAINS KODEPENA, 2024)
Graphic analysis tools and methods are very useful tools that can help quality managers shed light on developing problems and one that has an important role in control engineering methods is the Pareto Diagram, a simple chart that can provide actionable insight into how prioritize quality management resources that are maintained or improved. In the world of service-based work, this Pareto diagram is used to determine the level of importance that must be prioritized for improvements. The object of writing this scientific work is to examine how customer service from a company operating in the service sector achieves customer satisfaction. It is not easy for companies in the service sector to achieve customer satisfaction. There are various complaints that must be accommodated and considered in order to provide solutions so that the maximum level of customer trust is achieved. Keywords: Pareto, Quality, Satisfaction, Service, Control